Dynamic soluble changes in sVEGFR1, HGF, and VEGF promote chemotherapy and bevacizumab resistance: A prospective translational study in the BECOX (GEMCAD 09-01) trial. Issue 6 (May 2017) - Pineda, Estela; Salud, A; Vila-Navarro, E; Safont, MJ; Llorente, Beatriz; Aparicio, J; Vera, R; Escudero, P; Casado, E; Bosch, C; Bohn, U; Pérez-Carrión, R; et al.
Despite initial responsiveness, acquired resistance to both bevacizumab and chemotherapy in metastatic colorectal cancer is universal. We have recently published that in vitro, chronically oxaliplatin resistance upregulates soluble vascular endothelial growth factor receptor 1, downregulates vascular endothelial growth factor, and also promotes c-MET, b-catenin/transcription factor 4, and AKT activation. We tested whether variation in three serum biomarkers such as the natural c-MET ligand (hepatocyte growth factor), soluble vascular endothelial growth factor receptor 1, and vascular endothelial growth factor-A was associated with efficacy in metastatic colorectal cancer patients treated in the prospective BECOX study. Serum levels of vascular endothelial growth factor-A165, soluble vascular endothelial growth factor receptor 1, and hepatocyte growth factor were assessed by enzyme-linked immunosorbent assay method basally and every 3 cycles (at the time of computed tomography evaluation) in a preplanned translational study in the first-line BECOX trial in metastatic colorectal cancer patients treated with CAPOX plus bevacizumab. Response was evaluated by routine contrast-enhanced computed tomography by RECIST 1.1 by investigator assessment and by three blinded independent radiologists. Ratios between soluble vascular endothelial growth factor receptor 1/vascular endothelial growth factor-A and hepatocyte growth factor/vascular endothelial growth factor-A were established and variations through time were related to RECIST 1.1 by investigator assessment and independent radiologist. The BECOX trial included 68 patients, and 27 patients were analyzed in the translational trial. A total of 80 RECIST 1.1 evaluations were done by investigator assessment and 56 by independent radiologist. We found that a 3.22-fold increase in soluble vascular endothelial growth factor receptor 1/vascular endothelial growth factor-A by investigator assessment and a 3.06-fold increase in soluble vascular endothelial growth factor receptor 1/vascular endothelial growth factor-A by independent radiologist from previous determination were associated with responses compared with 1.38-fold increase by investigator assessment and 1.59 by independent radiologist in non-responders (p = 0.0009 and p = 0.03, respectively). Responders had a 3.36-fold increase in hepatocyte growth factor/vascular endothelial growth factor-A from previous determination by investigator assessment and 3.66-fold increase in hepatocyte growth factor/vascular endothelial growth factor-A by independent radiologist compared with 1.43-fold increase by investigator assessment and 1.53 by independent radiologist for non-responders (p = 0.002 and 0.003, respectively). In conclusion, a decrease in vascular endothelial growth factor-A and an increase in soluble vascular endothelial growth factor receptor 1 during chemotherapy and bevacizumab exposure can contribute to both chemotherapy (due to c-MET/b-catenin activation) and bevacizumab (due to low vascular endothelial growth factor requirements) resistance. Because hepatocyte growth factor levels decrease also during acquired resistance, alternative strategies to hepatocyte growth factor–ligand inhibition should be investigated.